Epidemiological study of Congenital Syphilis in the State of Pará from 2010 to 2021 - Caldas, Daniel dos Santos; Castillo, Jean Carlos Silva Del; Prazeres, Maria Clara Coelho; Colares, Túlio Vulcão; Omura, Lucas Yukio Emin; Pereira, Emanoele Saraiva (Seven Editora, 2023)
Introduction: Congenital syphilis is an infectious disease responsible for affecting the lives of thousands of Brazilian women and that, perceptibly, has been growing, even with the reality of underreporting in the country, due to the low quality of health care for such women. Objective: To evaluate the epidemiological profile of congenital syphilis in the state of Pará from 2010 to 2021. Methods: Descriptive and cross-sectional research of notified and confirmed cases of congenital syphilis, through the National System of Notifiable Diseases (SINAN). The variables were analyzed: health region, education, gender, age group, race, the performance of prenatal care, and treatment of the maternal partner. Results: Of the total of 7,595 cases, the highest occurrence was in the year 2019 (n = 945). Concepts up to six days old were the most affected age group (95.78%). Regarding the epidemiological characteristics of the genitor, the predominance was of brown color (82.57%) and who had prenatal care (84.6%). Untreated sexual partners totaled 4,663 (61.4%), approximately four times more than treated partners, 1,365 (18.0%). Conclusion: The study showed a significant increase in cases of the disease in the state of Pará, being the group of brown mothers with low education the most affected and with previously untreated partners. Moreover, it was evident that even with prenatal care the infection developed, confirming the fragile care system offered to pregnant women. Thus, this study contributes to helping the authorities in the creation and improvement of effective measures, since the relevant obstacles were addressed. DOI: https://doi.org/10.56238/colleinternhealthscienv1-134